An N‐terminal heterozygous missense CASK mutation is associated with microcephaly and bilateral retinal dystrophy plus optic nerve atrophy. Issue 1 (14th December 2018) - LaConte, Leslie E. W.; Chavan, Vrushali; DeLuca, Stephanie; Rubin, Karol; Malc, Jessica; Berry, Susan; Gail Summers, C.; Mukherjee, Konark
Abstract : Heterozygous loss‐of‐function mutations in the X‐linked gene CASK are associated with mental retardation and microcephaly with pontine and cerebellar hypoplasia (MICPCH) and ophthalmological disorders including optic nerve atrophy (ONA) and optic nerve hypoplasia (ONH). Recently, we have demonstrated that CASK (+/−) mice display ONH with 100% penetrance but exhibit no change in retinal lamination or structure. It is not clear if CASK loss‐of‐function predominantly affects retinal ganglion cells, or if other retinal cells like photoreceptors are also involved. Here, we report a heterozygous missense mutation in the N‐terminal calcium/calmodulin‐dependent kinase (CaMK) domain of the CASK protein in which a highly conserved leucine is mutated to the cyclic amino acid proline. In silico analysis suggests that the mutation may produce destabilizing structural changes. Experimentally, we observe pronounced misfolding and insolubility of the CASK L209P protein. Interestingly, the remaining soluble mutant protein fails to interact with Mint1, which specifically binds to CASK's CaMK domain, suggesting a mechanism for the phenotypes observed with the CASK L209P mutation. In addition to microcephaly, cerebellar hypoplasia and delayed development, the subject with the L209P mutation also presented with bilateral retinal dystrophy and ONA. Electroretinography indicated that rod photoreceptors are the most prominently affected cells. Our data suggest that the CASK interactions mediated by the CaMK domain may play a crucial role in retinal function, and thus, in addition to ONH, individuals with mutations in the CASK gene may exhibit other retinal disorders, depending on the nature of mutation.